MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS I DENGAN MODEl PROBING-PROMPTING DI SDN REGUNUNG 01 KECAMATAN TENGARAN KABUPATEN SEMARANG SEMESTER II TAHUN AJARAN 2015/2016 - Polianus Polianus; Slameto Slameto (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
Improving Learning Outcomes IPA Grade IV Model-prompting Probing in SDN Regunung Tengaran Semarang District 01 District 2 Semester academic year 2015/2016. Essay. Bachelor degree essay at PGSD the Faculty of Education Christian University Satya Discourse Salatiga. Supervisor Prof. Dr. Slameto, S.Pd., M.Pd. Classroom action research conducted in the fourth grade students of SDN Regunung Tengaran Semarang District 01 District Academic Year 2015/2016. The number of students as many as 26 people consisting of 16 male students and 10 female students. This study aims to improve learning outcomes using cooperative learning model Probing-prompting. This classroom action research conducted by two cycles, with one cycle of meetings to 2x and 1x reflection meeting. In each cycle consisting of planning, action, observation, evaluation and reflection. Collecting data in this study was conducted with a written test to calculate increase student learning outcomes IPA fourth grade. Improving student learning outcomes occur gradually, in which student learning outcomes on student learning outcomes prasiklus 23% the number of students 6 children, the first cycle of 73% with the number of students 19 0rang children, cycle II 96% by number of students 25 students. Thus, learning is successful 88%> 80% of the indicators of success. This shows that the type cooperative learning-prompting probing can improve student learning outcomes in grade IV SDN Regunng Tengaran Semarang District 01 District Academic Year 2015/2016.